The Cognitive Cost of Sad Films: Emotional Media and Decision-Making Impairment - Ahmad Taufiq (Winaya Inspirasi Nusantara Foundation, 2022)
The psychological and cognitive impacts of emotionally powerful films, especially those with melancholic themes, require further scrutiny in an age of pervasive media consumption. This study intends to systematically evaluate the current literature about the influence of sad-themed film consumption on daily decision-making processes. A critical review process was employed to analyse 38 peer-reviewed publications from prestigious journals in psychology, neuroscience, and media studies. The results indicate four principal thematic patterns: (1) emotional carryover effects that disrupt cognitive control, (2) sadness-induced alterations in risk perception and decision-making preferences, (3) media-induced cognitive fatigue after extended exposure, and (4) individual variances in susceptibility influenced by personality traits and emotional regulation abilities. The findings indicate that melancholic films may not only elicit emotional reactions but also subtly diminish cognitive performance, especially in tasks necessitating attention, judgement, and executive function. The research enhances the comprehensive understanding of media influences by connecting emotional and cognitive aspects. It underscores the necessity for enhanced understanding among viewers, educators, and doctors concerning the cognitive ramifications of emotionally charged media. Future study should empirically examine these interactions utilizing ecologically valid and longitudinal methodologies.